Legality and Legitimacy of Khatam Al-Quran: Study on Formalization of Islamic Law in Banjar Regency, South Kalimantan - Tobroni, Faiq; Nasrudin, Muhamad (UIN Sunan Kalijaga Yogyakarta, 2024)
This article identifies two forms of support for the formalization of Islamic law by examining the case of the Khatam Al-Qur'an in Banjar Regency, South Kalimantan. Using the theoretical framework of legal instrumentalism, it raises the question: how can the legality and legitimacy of the Khatam Al-Qur'an formalization in Banjar Regency be understood? From a legal standpoint, this formalization is valid and carries juridical authority within the framework of national law. Meanwhile, in terms of legitimacy, the policy enjoys strong public support as it is rooted in a local tradition known as Batamat—a deeply embedded cultural practice of Qur’anic completion ceremonies in Banjar society. Applying the theory of legal instrumentalism, this article finds that the formalization of Khatam Al-Qur`an has occurred through two complementary pathways. The first is the enactment of a regional regulation (Perda Khatam Al-Qur`an), which serves as the source of its legality. The second is the Batamat tradition, which provides the foundation for its legitimacy.